PEMBUATAN NUGGET JAMUR MERANG (Volvariella volvaceae) DENGAN PENAMBAHAN IKAN GABUS (Channa striata (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aimed to find out the best combination of straw mushroom and snakehead fish on nuggets production. A completely randomized design used with four treatments and four replications. The treatments consist of MG1 (100% straw mushroom : 0% snake head fish), MG2 (90% straw mushroom : 10% snake head fish), MG3 (80% straw mushroom : 20% snake head fish) and MG4 (70% straw mushroom : 30% snake head fish). The result showed that combination of straw mushroom and snakehead fish significantly affected the moisture content, fiber content, protein content and descriptive sensory assessment of colour, aroma, flavour and texture of nuggets. However its gave non significantly effect to ash content and overall hedonic test. The best treatment was MG4: 70% (straw mushroom: 30% snakehead fish) which content 53.82% water, 1.09% ash, 0.42% fiber, 7.82% protein, grayish white colour, rather straw mushroom aroma, a little distinctive flavour straw mushroom, rather chewy texture and overall hodonic assessment by panelist was “like” Keywords : Nuggets, straw mushroom, snakehead fish..